TATA KELOLA TEKNOLOGI INFORMASI - Ardi Hamzah (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2010)
Good information technology governance based on determining the level of integration and control of theorganization on information technology investment in a business organization. The existence of the organizationcontrolling the level of integration and harmony will create integration between information technology withbusiness activities ranging from line level, the functions and areas of the organization. In the initial stage, theintrinsic value of information technology should be incorporated fully into every aspect of the business not onlyon information technology functions. Given this, the need for strategic planning and good governance for theorganization and the alignment of information technology with organizational goals and taking into account theinternal and external resources. In the use of information technology is necessary for selection of goodinformation technology and organizational effectiveness. Use of information technology is based on thedetermination of policy, either through advice, regulatory and informational, on each line, function and areas ofthe organization. By conducting studies related to the performance of alignment usage of information technologyand business activities as well as further improving organizational performance.Keywords: information technology